Protocol for Site-Specific Photo-Crosslinking Proteomics to Identify Protein-Protein Interactions in Mammalian Cells - Chengjie Chen; Tao Peng (STAR Protocols, 2020)
Summary: Protein-protein interactions (PPIs) play essential roles in almost all aspects of cellular processes. However, PPIs remain challenging to study due to their substoichiometry, low affinity, dynamic nature, and context dependence. Here, we present a protocol for the capture and identification of PPIs in live mammalian cells, which relies on site-specific photo-crosslinking in live cells, affinity purification, and quantitative proteomics. The protocol facilitates efficient and reliable identification of the interacting proteins of a given protein of interest in live cells.For complete details on the use and execution of this protocol, please refer to Wu et al. (2020).